Application of neoclassical growth models to analysis of regional inequalities in Poland - Kliber, Paweł; Maćkowiak, Piotr; Malaga, Krzysztof (Economics and Business Review, 2004)
In this paper we apply the neoclassical growth models of Solow-Swan (1956) and Mankiw-Romer-Weil (1992) to the analysis of regional inequalities. The regional inequalities in Poland are described by the values of parameters in both of the growth models, the speed of convergence of the growth paths of GDP per worker (p.w.) towards their steady-states and the distributions of GDP p.w. among the sixteen Polish regions (voivod-ships) in 1999 - compared with their counterparts in the steady-states. We also try to evaluate the usefulness of the neoclassical growth models for the analysis of regional inequalities in Poland. (original abstract)